2012
DOI: 10.1016/j.bbrc.2012.08.082
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a is up-regulated in beta-cells by glucose and decreases glucose-stimulated insulin secretion

Abstract: Chronically elevated levels of glucose impair pancreatic beta-cell function while inducing beta-cell proliferation. MicroRNA-29a (miR-29a) levels are increased in several tissues in diabetic animals and mediate decreased insulin-stimulated glucose-transport of adipocytes. The aim was to investigate the impact of glucose on miR-29a levels in INS-1E beta-cells and in human islets of Langerhans and furthermore to evaluate the impact of miR-29a on beta-cell function and proliferation. Increased glucose levels up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 35 publications
7
92
2
4
Order By: Relevance
“…miR-29a and miR-29b contributed to the pancreatic beta cell-specific silencing of monocarboxylate transporter 1 [33]. More recently, Bagge et al [34] demonstrated that glucoseinduced upregulation of miR-29a reduced GSIS. He et al [35] Fig.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29a and miR-29b contributed to the pancreatic beta cell-specific silencing of monocarboxylate transporter 1 [33]. More recently, Bagge et al [34] demonstrated that glucoseinduced upregulation of miR-29a reduced GSIS. He et al [35] Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study did not show any marked effect of calorie-controlled diet therapy on miR-29a expres- sion. Previous reports have shown the roles of the miR-29 family in the reduction of glucose production, decreased glucose tolerance, and increased insulin synaptic exocytose in human INS-1E β cells (17,35) and in animal models (18). These findings suggest, to some extent, that there is a compensatory role of miR-29a in offsetting high circulating glucose and insulin resistance in obese diabetic humans.…”
Section: Discussionmentioning
confidence: 65%
“…These findings suggest, to some extent, that there is a compensatory role of miR-29a in offsetting high circulating glucose and insulin resistance in obese diabetic humans. Considering the pathophysiology of T2DM (36), since miR-29a affects the upstream genes of insulin secretion from the β-cells (17,18), we propose that more time is required to assess the probable results of diet therapies on the expression of miR-29a in obese T2DM subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown to influence myogenesis in chronic kidney disease (CKD) [16]. Moreover, mir-29a also regulates insulin secretion [17], manifestation of amyotrophic lateral sclerosis (ALS) disease [18], myocardial ischaemiareperfusion injury [19] and immune responses to intracellular bacterial infection [20]. During GM-CSF, IL-6 and Flt-3L mediated monocyte-macrophage differentiation, miR-29a levels are increased [21].…”
Section: Q1mentioning
confidence: 99%